Graduate students’ online academic information search behaviors in Taiwan (International Conference on Computers in Education, 2013)
Previous studies have found out that students’ search evaluating standards and search strategies play an important role in online information searching. Some studies indicated that there are only few studies discuss about graduate students’ online academic information search behaviors. Therefore, this study was conducted to assess these students’ online academic information search behaviors including search evaluating standards and search strategies. The interview findings were as a foundation to develop Online Academic Information Search Behaviors (OAISB) inventory, and then to explore the relationships between search evaluating standards and search strategies. The participants in this study included 296 graduate students in Taiwan. Results showed that the students with elaboration higher-level search strategies expressed multiple sources, deep as content, usefulness as technical and accessing as technical. And match lower-level search strategies attempt authority, surface as content, usefulness as technical and accessing as technical. In addition, the regression analyses revealed that graduate students’ online academic information search evaluating standards were viewed as predictors to explain their search strategies.